Plantain socio-productive system (Musa AAB): An initiative to revalue agriculture in western Antioquia - Ospina-Parra, Carlos Eduardo; Valencia-Montoya, Jorge Alberto; Cardona-Cardona, Jorge Enrique; Duque-Rios, Marcela; Usuga, Frank de Jesus; Alvarez Delgado, Carlos Andrés (Revista de Ciencias Agrícolas, 2025)
Scattered across all departments, plantain has long been a traditional crop within the Colombian peasant economy, making it fundamental to food security. The western region of the department of Antioquia has excellent production potential, given its optimal agroecological conditions and comparative advantages for production and marketing. However, emerging organizational processes, the loss of agricultural tradition, a lack of agro-industry, and inadequate soil and water management have hindered agricultural development. Mining extraction activities and agricultural production coexist in the region, leading competition for productive resources. De facto value chains provide an analytical and operational framework for identifying stakeholders, prioritizing technological limitations, and coordinating territorial and institutional stakeholders. Therefore, this research aimed to characterize plantain socio-productive units and value chains in the municipalities of Cañasgordas, Giraldo, Buriticá, and Santa Fe de Antioquia. The study was conducted in 2022 and 2023, following a qualitative descriptive method under multivariate analysis, social network analysis, and elements of the governance analytical framework. The production method is a low-tech system with a high potential for satisfying local and regional markets. Despite projects promoting plantain plantations, fundamental technological problems persist that must be addressed by building cross-cutting and specific capacities for co-validating technologies focused on generating quality plant material and managing pests and diseases.